The impact of context cues on college students’ purchase behavior for low-carbon products in CBEC - Wang, Chen; Zhou, Xiaolong; Zhang, Ran; Liu, Yexin (Frontiers in Psychology, 2023)
The purpose of this study is to examine the effects of online shopping context cues (price discount, carbon label and social commentary) on college students' trust / perceived risk and cross-border purchase intention (CBPI) for low-carbon products, and to compare the study between South Korea and Chinese college students. The theoretical framework is established by integrating S-O-R model and Valence framework. The variable of stimuli (S) is the driving force in the purchase behavior that influences the individual organism (O), and its subsequent response (R). Based on this logic, this study draws on the Valence framework to hypothesize effects of online shopping context cues (price discount, carbon label and social commentary) on college students' trust / perceived risk and cross-border purchase intention (CBPI) for low-carbon products. By conducting two online experiment-questionnaire studies and one between-subject lab experiment, we find that all three context cues have significant positive effects on trust and negative effects on perceived risk. College students' trust positively and perceived risk negatively impact college students' CBPI for low-carbon products. In addition, based on different cultures, languages and education, this study investigates the moderating effect of college students' nationality on their significant different cues processing modes for low-carbon products. The findings provide new insights into better understanding the factors affecting college students : South Korea versus China 删除[A]:low-carbon consumption behavior in a CBEC setting and have some practical implications.